Epidemiological situation of hepatitis A in Spain, 2021-2022 (Boletín Epidemiológico Semanal, 2023)
Introduction: The hepatitis A virus, which causes an acute liver infection, is transmitted by ingestion of food and water and direct person-to-person contact, especially among close contacts (cohabitants or other specific contexts such as kindergartens or men who have sex with men - MSM). The aim of this study was to describe the temporal trends and epidemiological characteristics of hepatitis A in 2021 and 2022 in Spain, comparing to data from previous years (2015-2020).Method: We analysed the cases of hepatitis A reported to the National Epidemiological Surveillance Network (RENAVE in Spanish) during the 2015-2022 period, calculating the annual cumulative incidences (CI), globally and by sex and age groups. The main characteristics of the hepatitis A outbreaks notified in 2021 and 2022 were also described.Results: In 2021 and 2022, the CI was 0.41 and 0.53 respectively, lower than those reported in previous years. No large differences were observed in the distribution between men and women. In 2021, the population group with the highest CI was adults > 44 years, while in 2022 was the population aged up to 15 years. In 2021 and 2022, the CI in population up to 44 years was fewer compared to 2015, while no large differences were observed for the older population.Conclusions: In 2021 and 2022, the hepatitis A CI was the minimum notified during the study period, with a significant decrease compared to previous years, especially in children and in population aged 15 to 44, possibly due to changes in the epidemiology of the disease by the COVID-19 pandemic and the exceptional situation of the outbreak of the years 2016-2017.
Keywords: hepatitis A; cumulative incidence; epidemiological surveillance; Spain